Search for dark matter signals towards a selection of recently detected DES dwarf galaxy satellites of the Milky Way with H.E.S.S. - Abdalla, Hassan; Bernlöhr, Konrad; Hinton, James Anthony; Hofmann, Werner; Jankowsky, Felix; Marx, Ramin; Quirrenbach, Andreas; Rieger, Frank M.; Schwemmer, Stephanie; Völk, Heinrich J.; Wagner, Stefan (Physical review, 2020)
Dwarf spheroidal galaxy satellites of the Milky Way are prime targets for indirect detection of dark matter with gamma rays due to their proximity, high dark matter content, and absence of nonthermal emission processes. Recently, the Dark Energy Survey (DES) revealed the existence of new ultrafaint dwarf spheroidal galaxies in the southern-hemisphere sky, therefore ideally located for ground-based observations with the imaging atmospheric Cherenkov telescope array H.E.S.S. We present a search for very-high-energy (E≳100  GeV) gamma-ray emission using H.E.S.S. observations carried out recently towards Reticulum II, Tucana II, Tucana III, Tucana IV, and Grus II satellites. No significant very-high-energy gamma-ray excess is found from the observations on any individual object nor in the combined analysis of all the datasets. Using the most recent modeling of the dark matter distribution in the dwarf galaxy halo, we compute for the first time on DES satellites individual and combined constraints from Cherenkov telescope observations on the annihilation cross section of dark matter particles in the form of Weakly Interacting Massive Particles. The combined 95% C.L. observed upper limits reach ⟨σv⟩≃1×10−23  cm3 s−1 in the W+W− channel and 4×10−26  cm3 s−1 in the γγ channels for a dark matter mass of 1.5 TeV. The H.E.S.S. constraints well complement the results from Fermi-LAT, HAWC, MAGIC, and VERITAS and are currently the most stringent in the γγ channels in the multi-GeV/multi-TeV mass range.